A Step-By-Step Tutorial for Performing a Moderated Mediation Analysis using PROCESS - Clement, Leah Mary; Bradley-Garcia, Meenakshie (Tutorials in quantitative methods for psychology, 2022)
Interest in moderation and mediation models have gained momentum since the 1980s and have become widespread in numerous fields of research including clinical, social, and health psychology in addition to behavioral, educational, and organizational research. There are resources available to help the user understand an analysis of a moderated mediation using the PROCESS macro and its resultant output, however, many are in video format (e.g., YouTube) or lack detailed instructions based on real world examples. To our knowledge, there are no resources that provide a thorough yet accessible step-by-step explanation of the procedure involved in using PROCESS v4.1 to analyze and interpret a moderated mediation model using real data in SPSS v28. The aim of this guide is to address this knowledge gap. An overview of mediation, moderation, and moderated mediation models is presented followed by instructions for verifying that assumptions are respected. Finally, a procedure to analyze data using PROCESS v4.1 is presented along with an interpretation of the resultant output.